The Minor Adjustment Beauty Salon [compact disc, unabridged] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series, 2013)
Precious Ramotswe is asked to help the proprietor of the Minor Adjustment Beauty Salon, who is having trouble with her business. The salon has suffered some unfortunate events, including face cream that burns the skin. Could someone be trying to put the salon out of business? Meanwhile, on the home front, Grace Makutsi is going to have a baby. But in Botswana--a land where family has always been held above all else but which is on the crossroads between old and new--this may be cause for as much controversy as celebration.